Measuring ‘Brand Love’ : Understanding the Attitude of Millennials towards Select Brands - Sathyanarayana, B K; Kishor, Nawal (Ushus Journal of Business Management, 2014)
Contemporary management practices indicate that many successful companies have recognised the strategic importance of human resources. The assumption emphasising the practice of SHRM is that people are the organization’s vital resource and organizational performance largely depends on them. It is, therefore, appropriate that HRM policies and practices is formulated and executed effectively, so that HRM will make a substantial impact on firm performance. SHRM aims at to ensure that HRM is fully integrated with the strategy and the strategic needs of the firm, human resource policies are consistent both across hierarchies and human resource practices are adjusted, accepted and used by line managers and employees as part of their everyday work. The impact of the SHRM practices in an organization will decide the survival and growth of the organization itself.